(THE RETRACTION REQUESTED BY THE AUTHOR) CLIL-ORIENTED AND TASK-BASED EFL MATERIALS DEVELOPMENT - Suhandoko Suhandoko (Eltin Journal : Journal of English Language Teaching in Indonesia, 2020)
This Research & Development (R&D) aims at developing materials in the form of a coursebook prototype for the tenth-grade students of senior high schools in Indonesia. Teacher interviews and students questionnaire were used to assess the users’ needs. The data revealed that the existing materials are not relevant to the students’ needs majored in studying Math and Science (Biology, Chemistry, Physics). So there is a need for developing new materials by orienting to quality CLIL materials principles and task-based approach. In general, based on the validation checklists, the materials were considered reliable by the English teachers, the EFL material and language expert and the media expert. The final product was also considered acceptable by the students and teachers based on the questionnaires distributed after the limited-field tryout. The study resulted in three main products: Student Book, Teacher’s Guide, and Listening Audio CD.